Marcación explícita de foco estrecho en español - Mora Bustos, Armando (El Colegio de México, 2009)
In Bogotá Spanish, people frequently uses sentences with ser. Usually ser appears in cleft sentences, but in this Spanish variety ser is not a verb, it is a particle that focalizes the post verbal constituent. The syntactic, semantic and pragmatic characteristics of this particle are similar to analogous ones found in African languages (Bantu and mande) and also in Quechua. In general, in these languages there is a direct correlation betwen word order structure and foci. Specifically, in Bogotá Spanish, the correlations are among word order flexibility and the particle ser’s constrictions. In other words, a transitive subject will bear focus only if it can move to the post verbal position, so it can be modified by the particle ser’s scope.